Canine OHE - Weir, Heather, speaker; Colorado State University. College of Veterinary Medicine, producer (Colorado State University. Libraries, 2002)
Historic document - content may not reflect current scientific research, policies, or practices.
From DVD titled "Canine and Feline Elective Surgery," copy 4.
Accessibility features: Transcript.
Keywords: Dogs -- Surgery; Surgery, Veterinary -- Methods